Criminal Law and Criminology: A Survey of Recent Books. - Ferrall, Bard R. (Journal of Criminal Law & Criminology)
Twelve books dealing with various issues in criminal law and criminology are reviewed. The books are The Death Penalty: An American History, by Stuart Banner; Beyond Repair? America's Death Penalty, edited by Stephen P. Garvey; Miranda's Waning Protections: Police Interrogation Practices After Dickerson, by Welsh E. White; The Cambridge Handbook of Australian Criminology, edited by Adam Graycar and Peter Grabosky; One of the Guys: Girls, Gangs and Gender, by Jody Miller; Ratting: The Use and Abuse of Informants in the American Justice System, by Robert M. Bloom; Can Gun Control Work?, by James B. Jacobs; Guns and Violence: The English Experience, by Joyce Lee Malcolm; Making Hate a Crime: From Social Movement to Law Enforcement, by Valerie Jenness and Ryken Grattet; Punishing Juveniles: Principles and Critique, edited by Ido Weijers and Antony Duff; “Whores and Thieves of the Worst Kind”: A Study of Women, Crime, and Prisons, 1835–2000, by L. Mara Dodge; and Privatization in Criminal Justice: Past, Present and Future, by David Shichor and Michael J. Gilbert.